Predictive control : fundamentals and developments - Xi, Yugeng, 1946-; Li, Dewei (Computer scientist) (John Wiley & Sons Singapore Pte. Ltd, 2019)
"Systematically introduces fundamental concepts, basic algorithms, and applications of MPC -Includes a comprehensive overview of MPC development, emphasizing recent advances and modern approaches - Features numerous MPC models and structures, based on rigorous research -Based on the best-selling Chinese edition, which has become a cornerstone in the Chinese market Modeling Predictive Control (MPC) is an advanced control technology that can effectively handle optimization control under constraints. Since MPC appeared in the industrial process control field in the 1970's, the demand for constrained optimization control, in particular MPC, in various application fields has been increasing continuously. The MPC application fields extend from traditional oil refinery, petrochemical, and chemical industries, to almost all fields such as power systems, manufacturing, aerospace, electromechanics, urban transportation, agricultural greenhouse, and medicine etc. MPC has the ability to anticipate future events and can take control actions accordingly. PID and LQR controllers do not have this predictive ability. MPC is nearly universally implemented as a digital control, although there is research into achieving faster response times with specially designed analog circuitry"--